ANALISIS PENGARUH USIA, JUMLAH PINJAMAN, PENGALAMAN USAHA DAN OMZET USAHA TERHADAP KELANCARAN ANGSURAN PEMBIAYAAN ULTRA MIKRO (UMi) - Andrianto, Toni; Nurjanah, Yayuk (Institut Bisnis dan Informatika Kesatuan, 2023)
The purpose of this research is to develop a predictive model for the probability of default from Ultra Micro financing customers (UMi) which was initiated by the Government Investment Agency of the Ministry of Finance of the Republic of Indonesia in 2017. The analytical method uses Logistics Regression (Logit) as binary logit by sampling observational data. in 2021 by purposive sampling as many as 398 debtors consisting of 46 defaulted debtors and 352 current debtors. The dependent variable uses binary data with dummy